BAZNAS Contribution Through Productive Zakat Program to the Economy Poor Society - Ashari, Azis; Fatwati, Siti Rohma; Hasanah, Sofiatul; Juwairiyah, Siti; Rudi, Rudi; Utama, Aris Putra (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This research aims to know the role of zakat productive in empowering poor communities identified as mustahik in entrepreneurship. Zakat which is allocated for mustahik can be used as venture capital whereas businesses developed by mustahik are generally still small-scale, which is not accessible by the bank. The mentoring process includes planning, implementation, monitoring, and control as well as an evaluation of the program, becoming one of the board programs to manage productive zakat, so the expectation of creating economic circulation, increasing the productivity of the business community, and increasing revenue/economic outcomes will sustainable. The method used in this study is a descriptive qualitative method to see the influence of zakat productive to the empowerment of the poor through the poverty index. This research uses primary data and secondary data. Primary data obtained from the survey results from the results of the dissemination of the questionnaire, and conduct in-depth interviews with program managers Productive Zakat in Baznas and mustahik as community empowerment program participants through Productive Zakat. Secondary data was obtained from the report Program BAZNAS on the internet, some literature, and articles. The results of the study showed overall mustahik said BAZNAS's productive economic program has been running very well.